Le développement de la japonologie en France dans les années 1920 : autour de la revue Japon et Extrême-Orient - Christophe Marquet (Ebisu: Études Japonaises, 2014)
In France, World War I signalled both the decline of Japonism in the arts and a new interest in contemporary Japan. In 1923, Claude Eugène Maitre (1876-1925), former head of the École française d’Extrême-Orient, launched the journal Japon et Extrême-Orient to provide French readers with “as much and as far as possible precise information on a country to which they are naturally drawn but know little about […]”. Though short-lived, this eclectic journal gives an idea of the state of Japanese Studies in the early 1920s and the level of information on Japan available in France at the time. Through the journal, pioneering Japanologists like Serge Elisséev and Moïse Charles Haguenauer spread knowledge of modern and contemporary Japan in order to encourage intellectual exchange between the two countries.